KONSEP-KONSEP DASAR TERAPI KOGNITIF UNTUK MENGATASI DEPRESI - Seralarat, Kornelis (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2018)
Depression is one of mood disorders due to intense sadness, hopeless and withdrawal from others which disrupts daily activities and behavior. The purpose of this study is to analyze and explain the usefulness of Cognitive Therapy in dealing with depressed clients. Cognitive therapy is a process of treatment to help client to correct his faulty belief and thinking that can impact on client’s emotion and behavior. Many studies have shown that Cognitive Therapy is useful for dealing with patients who are depressed.